SOME TYPES OF CONTIONUOUS FUNCTION VIA (r0, s1)-FUZZY αm- CLOSED SETS - Fatimah M. Mohammed; Sanaa I. Abdullah (Tikrit Journal of Pure Science)
The purpose of this paper is to introduce and study the notions of  some types of continuous functions via (r0, s1)-fuzzy αm-closed sets in double fuzzy topological space. Also, we reached some relationships among these new types of functions and compare them with their opposite with illustrative examples in the same space